A new wide bandgap small molecular acceptor based on indenofluorene derivatives for fullerene-free organic solar cells. (May 2017) - Zhang, Jie; Zhao, Baofeng; Mi, Yuhua; Liu, Hongli; Guo, Zhaoqi; Bie, Guojun; Wei, Wei; Gao, Chao; An, Zhongwei
Abstract: An efficient wide bandgap small molecular electron acceptor 2, 2'-((2Z, 2′Z)-(((6, 6, 12, 12-tetraoctyl-6, 12-dihydroindeno[1, 2- b ]fluorene-2, 8-diyl)bis(thiophene-5, 2-diyl))bis(methanylylidene))bis(3-oxo-2, 3-dihydro-1H-indene-2, 1-diylidene))dimalononitrile (IFTIC ) based on indenofluorene for organic solar cells was developed. With strong and broad absorption in shortwave region (470–690 nm) and suitable energy levels (HOMO = −5.42 eV, LUMO = −3.85 eV), this newly designed wide bandgap acceptor was able to preferably match the most typical low bandgap polymer donor material poly({4, 8-bis[(5-(2-ethylhexyl)-2-thienyl]benzo[1, 2- b :4, 5- b ′]dithiophene-2, 6-diyl}{3-fluoro-2-[(2-ethylhexyl)carbonyl]thieno[3, 4- b ]thiophenediyl}) (PTB7-Th ). Benefit from its up-shifted LUMO energy level and complementary absorption spectrum, the inverted device based onIFTIC andPTB7-Th processed power conversion efficiencies (PCE) up to 6.56% and relatively high open circuit voltage ( Voc ) value (0.92 V). These results demonstrate that the indenofluorene type wide bandgap small molecule could be the promising electron acceptor in organic solar cells. Highlights: A new fullerene-free acceptor (IFTIC) based on indenofluorene was synthesized. IFTIC possesses relatively wide bandgap of 1.82 eV and high LUMO energy level of −3.85 eV. A power conversion efficiency of 6.56% was obtained for the optimal device of IFTIC blended with PTB7-Th.